Profile, knowledge, attitude and perceptions of caregivers of patients on blood donation in a tertiary government hospital - Cañada, Fatima Anna Gracia; Macatangay, Daisy Monica; Marquez, Katharene Phoebe; Matias, Jayvee; Paz, Eddisson Jospeh; Ramos, Mar Angelo
The National Blood Services Act of 1994”, RA 7719 was enacted to promote voluntary non-remunerated blood donation. It aims to instill public consciousness of the principle that blood donation is a humanitarian act. In reality, however, demand for blood products far outweighs the blood supply of the country. In this regard, it is important to look at the factors that influence the behavior of a person to donate or not to donate blood voluntarily. This study aimed to determine the profile, knowledge, attitude and perceptions of caregivers of patients regarding blood donation. The study utilized a descriptive, correlational research design. The settings of the study were selected wards in a tertiary government hospital. Sampling method used was systematic sampling. The researchers revised an existing tool to use as a survey-questionnaire then administered it to caregivers of patients who gave their consent. A total of 113 out of 150 questionnaires were retrieved. The data gathered were analyzed using descriptive statistics and to determine the strength of relationship between age and education; attainment and the caregivers’ level of knowledge and perception, the Spearman's rank correlation coefficient was utilized. The caregivers in a tertiary government hospital setting is predominantly female (n=68 or 60.2%), non-donor (n=80 or 71%), with a mean age of 31.27 years, Roman Catholic (n=90 or 80%), high school graduate (n=43 or 38%), either spouse (n=26 or 23%) or not related to the patient (n=28 or 24.8%) and with a full-time job. (n=28 or 28%) The attitude of 45% of non-donor caregivers (n=51) towards blood donation is negative, meaning they would rather not donate blood to a blood bank. Majority of donors (n=27, 24%) have positive attitude. Primary motivating factors for both groups were extrinsic motives, or those that are based in the actions of others, such as rewards and incentives and social pressure (Holdershaw, 2005). These are to have free time from work, influence through advertisements on Posters, fliers, newspapers and radios, interest to learn their blood type and encouragement from family and friends, to name some. While the most common hindering factors for donors and non-donors were because they were never been offered or asked to do so, fear of needle, health reasons or conditions and insufficient information regarding blood donation. In terms of knowledge, 29% (n=33) of caregivers know very little about blood donation. Almost all, or 94% (n=106) of caregivers, however, have good perception on blood donation. Findings also showed that there is a positive relationship between level of knowledge and level of perception (r= 0.386 at 0.01 level of confidence). There is also a significant relationship between age and level of knowledge (r= 0.251 at 0.01 level of confidence). As recommendations, education and campaign on blood donation should be done with new strategies taking into consideration the above findings. With many of the people having good perception on blood donation, it would be easier to target and motivate them if they are provided with enough knowledge about the qualifications of a donor, the process and the places to go where they can donate. Increasing the people’s knowledge to keep them informed on the basics of blood donation is a good supplement in the campaigns of encouraging people to donate blood. Knowledge provides empowerment and possible blood donors could feel better about themselves knowing that they have made an informed choice. These actions in turn could lead to increase the development of a positive attitude towards voluntary, non-remunerated blood donation.